Falls and fear of falling among elderly persons living in the community: occupational therapy interventions. - Walker JE; Howland J (American Journal of Occupational Therapy, 1991)
Each year, about one third of the population over 65 years of age experiences at least one fall (Perry, 1982). Assessment of the incidence of falls and the prevalence, intensity, and covariates of fear of falling among community-based elderly persons was conducted through interviews of 115 residents in a housing development (mean age = 78 years). Fifty-three percent reported having fallen in recent years, 32% in the last year. Fear of falling ranked first when compared with other common fears. In a logistic regression model predicting limitation of activity independent of risk factors for falling, fear of falling was marginally significant (p = .06). The results of the study show that falls are frequent and fear of falling prevalent among the community-based elderly. A comprehensive program designed to reduce the risk of falls is presented.